Luxemburger an der Universität Fribourg unter der Ägide von Johann Peter Kirsch: Studenten - Freunde - Weggefährten - Mossong, Isabelle (Römische Quartalschrift für christliche Altertumskunde und Kirchengeschichte, 2025)
"Luxembourgers at Fribourg University under the aegis of J. P. Kirsch. Students - Friends - Companions" - Immediately after the university was founded in 1890, a young Luxembourgish priest came to Fribourg to take up the chair of patrology and Christian archaeology. J. P. Kirsch not only brought with him the network he had been able to build up in Rome a few years earlier, but he was also followed by a whole series of Luxembourgish students who took up studies at one of the four faculties of the young university. These biographies often reflect Kirsch's influence; some of these young people completed their doctoral studies in Fribourg and later remained in Kirsch's network. This article takes a look at eight biographies whose academic achievements made them significant for the Fribourg university community as well as for the Luxembourgish educated middle classes at the beginning of the 20th century.